2016
DOI: 10.1016/s0140-6736(15)00805-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intensive blood pressure lowering on cardiovascular and renal outcomes: updated systematic review and meta-analysis

Abstract: National Health and Medical Research Council of Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
515
5
26

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 861 publications
(569 citation statements)
references
References 41 publications
23
515
5
26
Order By: Relevance
“…In addition, there is little guidance on how to interpret the 2017 ACC/AHA clinical guidelines on hypertension as they apply to pregnancy. The 2017 ACC/AHA guidelines stemmed from recent clinical trials that have demonstrated that achieving intensive BP reduction (systolic BP <120 mm Hg) resulted in a significant decrease in the risk of CVD events and mortality compared with BP reduction to within the range currently termed stage 1 hypertension (systolic BP 130–139 mm Hg or diastolic BP 80–89 mm Hg) 66, 67, 68. The threshold for BP treatment in pregnancy is higher, generally above systolic BP 150 to 160 mm Hg and diastolic BP 95 to 110 mm Hg.…”
Section: Current Guidelines and Recommendationsmentioning
confidence: 99%
“…In addition, there is little guidance on how to interpret the 2017 ACC/AHA clinical guidelines on hypertension as they apply to pregnancy. The 2017 ACC/AHA guidelines stemmed from recent clinical trials that have demonstrated that achieving intensive BP reduction (systolic BP <120 mm Hg) resulted in a significant decrease in the risk of CVD events and mortality compared with BP reduction to within the range currently termed stage 1 hypertension (systolic BP 130–139 mm Hg or diastolic BP 80–89 mm Hg) 66, 67, 68. The threshold for BP treatment in pregnancy is higher, generally above systolic BP 150 to 160 mm Hg and diastolic BP 95 to 110 mm Hg.…”
Section: Current Guidelines and Recommendationsmentioning
confidence: 99%
“…A recent systematic review and meta‐analysis of 19 trials suggested that intensive blood pressure lowering, including targeting SBP/DBP lower than current recommendations, has further protective effects against major cardiovascular events 14. The recent Systolic Blood Pressure Intervention Trial (SPRINT) showed that with treatment targeting an SBP of less than 120 mm Hg compared with 140 mm Hg, nondiabetic adults aged 50 and above at high risk for cardiovascular events had lower rates of all‐cause mortality and major cardiovascular events15; in prespecified subgroup analysis, this benefit was similarly observed among those aged 75 years or older 16.…”
Section: Introductionmentioning
confidence: 99%
“…Beginning in the 1960s, randomized controlled trials demonstrated the value of treating high diastolic blood pressure and, subsequently, high systolic blood pressure (SBP) 1, 2. However, the treatment target for SBP has been uncertain 3, 4.…”
mentioning
confidence: 99%
“…However, the treatment target for SBP has been uncertain 3, 4. Several recent meta‐analyses support “intensive” SBP lowering in patients with and without diabetes mellitus, but these included randomized controlled trials that targeted a higher SBP goal (<140 mm Hg or even higher) for “intensive” SBP control or blood pressure medication trials that did not have a predefined SBP goal 2, 5, 6, 7. The recent American College of Cardiology/American Heart Association guidelines recommend an SBP goal of <130 mm Hg in patients with and without diabetes mellitus 8…”
mentioning
confidence: 99%